Warak Dugder Dance: Feminism and the Existence of Women as Strengthening the Existence of the Performing Arts - Mawasti, Frihastyayu Bintyar; Malarsih, Malarsih; Hartono, Hartno (Catharsis, 2020)
The Warak Dugder dance is a new creation dance inspired by the dugderan tradition in welcoming the month of Ramadan in Semarang City. The purpose of this research is to analyze feminism and the role of women in the performing arts of Warak Dugder Dance, Semarang City. This research uses qualitative research methods with an anthropological approach. The data analysis used to analyze the feminism of the Warak Dugder Dance consists of three lines, namely: data reduction, data presentation, and conclusion drawing. The data collection techniques using observation, interview, and documentation techniques. The results show that the Warak Dugder Dance illustrates the excitement of the atmosphere of the dugderan ritual ceremony in the Semarang city by adapting the characteristics and culture of the multicultural people of Semarang City. Feminism in the Warak Dugder Dance is a feminism of a radical-cultural field, which means that a woman does not need to be like a man, women still have strength that focus on tenderness, and women are the owners of their own bodies. The movement of female dancers rejecting male dancers in the Warak Dugder Dance illustrates the power of women to protect themselves and their honor. The Warak Dugder dance is often performed only displays female dancers, it proofs that female dancers have a role in strengthening the existence of the Warak Dugder Dance. The benefit of this research is to provide information related to the concept of feminism and the contribution of female dancers in the Warak Dugder Dance, the motivator for the community's enthusiasm to continue to preserve the regional arts of Semarang City, especially the Warak Dugder Dance, and to confirm that female dancers play a role in the existence of the Warak Dugder Dance.